PIPAT TRADITION IN MAINLAND SOUTHEAST ASIAN NATIONS: TRADITIONAL MUSIC IN THAILAND AND CAMBODIA - Manop Wisuttipat (LPPMPP Institut Seni Indonesia Padangpanjang, 2011)
Pipat tradition would be referred to a type of traditional music which was once court music in Thailand. At present, the tradition is abundantly in practice in central Thailand. The details of Pipat tradition are discussed briefly in different perspectives in order to understand the whole panorama of the present Pipat tradition phenomena. In the post-genocidal war era, Pinpeat still prevails and retains its strength culturally. It can be reflected from widespread, intensive practice of the tradition in ritual or ceremony, as part of Cambodian way of life. The emergence of Donti Puenmuang has a great effect to the court Pinpat tradition in many facets.